Determinants of compliance to therapeutic regimen among selected Filipino juvenile diabetics - Cruz, Jayvee G.
By the end of the century, more than one hundred million people will have diabetes. Much of the increase will come from underdeveloped and underprivileged communities like the Philippines. Juvenile diabetes, the type which afflicts children and young adults, constitute approximately twenty percent of the entire diabetic populace.Compliance to the therapeutic regimen among these age groups persists as a challenge for nurses and other members of the health care team. If their condition remains poorly controlled, the unwanted and almost fatal complications will be evident in ten years. This study has attempted to identify the determinants of compliance to the therapeutic regimen among selected Filipino juvenile diabetics.The study's conceptual framework is premised on the fact that therapeutic regimen is prescribed to improve the condition of those having diabetes. The variables investigated in this study are: demographic variables, regimen-associated variables and psychosocial variables. They are hypothesized as determinants to the compliant behavior of diabetic clients.This study utilized the non-experimental, descriptive design. The sampling method used was purposive with snowball techniques. The participants totaling to 85 juvenile diabetics came from the diabetic clinics in Metro Manila, namely: the Juvenile Diabetes Foundation, Incorporated clinic at the Lung Center of the Philippines, the Institute for Studies on Diabetes Foundation, Incorporated clinic at the University of the East Ramon Magsaysay Memorial Medical Center and at the St. Luke's Medical Center.The instrument consisted of two sets of questionaires. The first part elicited information on the different factors that may affect the compliance of the participants on the therapeutic regimen. The second part focused on the participants' evaluation of self-esteem and body image.Descriptive statistics such as the mean, mode and percentages were utilized to analyze the data that described certain behavioral phenomena. These enhanced the significance of the variables under investigation. Inferential statistics such as the relational Chi-square and Fisher's Exact Test were applied to determine which among certain variables significantly relate with the compliance behavior of participants. To predict variables towards compliance to therapeutic regimen, the Forward Wald Logistics Regression was used.Level of significance was preset at .05.The significant findings of the study revealed that the presence of problems with diet and income were the best predictor of compliance to diet among all the variables investigated. These accounted 39of the variance in compliance. On compliance to exercise regimen, significantpredictors are frequency of exercise, and the perception that bodily changes affected body-image and self-esteem. Together, these variables explain 43of the variance in the compliance toward exercise regimen.